Confidential and legal access to abortion and contraception in the United States, 1960-2020 - Caitlin Knowles Myers (Global Labor Organization (GLO), 2022)
An expansive empirical literature estimates the causal effects of policies governing young women's confidential and legal access to contraception and abortion. I present a new review of changes in the historical policy environment in the United States that serve as the foundation of this work. I consult primary sources including annotated statutes, judicial rulings, attorney general opinions, and advisory articles in medical journals, as well as secondary sources including newspaper articles and snapshots of various policy environments prepared by scholars, advocates, and government organizations. Based on this review, I provide a suggested coding of the policy environment over the past 60 years. I also present and compare the legal coding schemes used in the empirical literature and where possible I resolve numerous and substantial discrepancies.
Keywords: J13; J18; 330; Contraception; abortion; policy